Epigenetic factors in breast cancer therapy - Mathur, Runjhun; Jha, Niraj Kumar; Saini, Gaurav; Jha, Saurabh Kumar; Shukla, Sheo Prasad; Filipejová, Zita; Kesari, Kavindra Kumar; Iqbal, Danish; Nand, Parma; Upadhye, Vijay Jagdish; Jha, Abhimanyu Kumar; Roychoudhury, Shubhadeep; et al. (Frontiers in Genetics, 2022)
Abstract Epigenetic modifications are inherited differences in cellular phenotypes, such as cell gene expression alterations, that occur during somatic cell divisions (also, in rare circumstances, in germ line transmission), but no alterations to the DNA sequence are involved. Histone alterations, polycomb/trithorax associated proteins, short non-coding or short RNAs, long non - coding RNAs (lncRNAs), & DNA methylation are just a few biological processes involved in epigenetic events. These various modifications are intricately linked. The transcriptional potential of genes is closely conditioned by epigenetic control, which is crucial in normal growth and development. Epigenetic mechanisms transmit genomic adaptation to an environment, resulting in a specific phenotype. The purpose of this systematic review is to glance at the roles of Estrogen signalling, polycomb/trithorax associated proteins, , DNA methylation in breast cancer progression, as well as epigenetic mechanisms in breast cancer therapy, with an emphasis on functionality, regulatory factors, therapeutic value, and future challenges.